Analyzing Character Value Integration in ESP Materials for Computer Science - Maru Mary Jones Panjaitan (Universitas Advent Surya Nusantara, 2025)
This study explores the incorporation of character values within English for Specific Purposes (ESP) materials aimed at Computer Science students, highlighting their essential role in equipping learners to address ethical issues in the technology industry. Identified character values include ethical responsibility, communication skills, critical thinking, teamwork, and professionalism. The research finds that these values are effectively integrated into the curriculum through focused course design, hands-on learning activities, and assessment methods. Nevertheless, some gaps exist, particularly in deepening discussions around ethics and providing adequate real-world examples. Feedback from educators and students shows a shared acknowledgment of the significance of character education, though students often seek more practical applications. Suggestions for enhancement include promoting interdisciplinary collaboration, creating robust assessment methods, and offering professional development for instructors. The study concludes with recommendations for future research, emphasizing the exploration of ethical complexity, the effectiveness of practical applications, and the long-term effects of character education on graduates' career success. It advocates for a comprehensive approach to character education that produces responsible and skilled professionals in the digital era. Key words: Character Values, English for Specific Purposes (ESP), Computer Science